Effectiveness of manual physical therapy in the treatment of cervical radiculopathy: a systematic review - Boyles, Robert (Maney Publishing, 2011)
STUDY DESIGN: Systematic review of randomized clinical trials. OBJECTIVE: Review of current literature regarding the effectiveness of manual therapy in the treatment of cervical radiculopathy. BACKGROUND: Cervical radiculopathy (CR) is a clinical condition frequently encountered in the physical therapy clinic. Cervical radiculopathy is a result of space occupying lesions in the cervical spine: either cervical disc herniations, spondylosis, or osteophytosis. These affect the pain generators of bony and ligamentous tissues, producing radicular symptoms (i.e. pain, numbness, weakness, paresthesia) observed in the upper extremity of patients with cervical nerve root pathology. Cervical radiculopathy has a reported annual incidence of 83·2 per 100 000 and an increased prevalence in the fifth decade of life among the general population. RESULTS: Medline and CINAHL via EBSCO, Cochrane Library, and Google Scholar were used to retrieve the randomized clinical trial studies for this review between the years of 1995 and February of 2011. Four studies met inclusion criteria and were considered to be high quality (PEDro scores of ⩾5). Manual therapy techniques included muscle energy techniques, non-thrust/thrust manipulation/mobilization of the cervical and/or thoracic spine, soft-tissue mobilization, and neural mobilization. In each study, manual therapy was either a stand-alone intervention or part of a multimodal approach which included therapeutic exercise and often some form of cervical traction. Although no clear cause and effect relationship can be established between improvement in radicular symptoms and manual therapy, results are generally promising. CONCLUSION: Although a definitive treatment progression for treating CR has not been developed a general consensus exists within the literature that using manual therapy techniques in conjunction with therapeutic exercise is effective in regard to increasing function, as well as AROM, while decreasing levels of pain and disability. High quality RCTs featuring control groups are necessary to establish clear and effective protocols in the treatment of CR.